SOSIALISASI PENCEGAHAN DAN PERLINDUNGAN HUKUM TERHADAP KORBAN KEKERASAN DALAM RUMAH TANGGA (KDRT) - Syaifullah, Syaifullah; Guntara, Bima; Dadang, Dadang; Hendra, Rio; Sianipar, Ferry Agus (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2021)
Domestic violence is an act of violence against women that is often invisible. Along with cases of domestic violence that are increasing day by day, the government issued a Law on the Elimination of Domestic Violence, with the aim that victims of domestic violence, especially women, are expected to obtain legal protection. The problem that arises then is how to protect the law against victims of Domestic Violence (KDRT) to prevent criminal acts of domestic violence. The existence of Law Number 23 of 2004 concerning the Elimination of Domestic Violence is expected to be able to provide significant legal protection for victims of Domestic Violence (KDRT). The forms of protection regulated in this law are temporary protection from the police, court protection and placement of victims in "safe houses". However, the results of research, both through District Court decisions and informants, show that the form of protection for victims of domestic violence is still dominant through repressive actions (imprisonment sentences) to perpetrators, while temporary protection and permanent protection from the courts are less attention Domestic violence is an act of violence against physical, psychological, sexual and neglect in the family. Law Number 23 of 2004 concerning the Elimination of Domestic Violence (PKDRT) has regulated the protection for victims, but it does not fully fulfill the rights of victims. Criminal action, which is the goal of the Domestic Violence Law, often has a negative impact on victims, including: divorce and domestic disharmony. In addition, the imposition of a criminal offense is also contrary to other objectives to be achieved by the Act, namely: the maintenance of a harmonious and prosperous household. The PKDRT law provides opportunities for the involvement of the government, victims and the community in accordance with the idea of restorative justice which is already known by the Indonesian people as a form of local wisdom, but the protection of victims has not been fulfilled. Meanwhile, if the crime will be used in resolving domestic violence cases, it must be as selective as possible, especially if the consequences of the acts of the perpetrators of domestic violence will threaten and endanger the survival of the victim. Regarding forms of violence, violence is not merely physical in nature such as: beatings, torture or torture which easily leaves visible evidence. In many ways violence always takes many forms as well as many dimensions. Psychological violence such as constant fear, receiving threats, making someone feel humiliated, is another form that is very difficult to prove but leaves a long imprint on everyone's memory.